Seven Shades of Black Thoughts: COVID-19 and Its Psychological Consequences on Cancer Patients - Garutti, Mattia; Cortiula, Francesco; Puglisi, Fabio (Frontiers in Oncology, 2020)
An outbreak of novel coronavirus disease (COVID-19) that started in China at the end of 2019 has rapidly spread all over the world. COVID-19 is plaguing people not only physically but also psychologically, and cancer patients are particularly exposed to this emotional threat. Herein, we describe the psychological threats posed by COVID-19 to cancer patients. Our analysis is based on the concerns of our patients during our daily clinical interactions in both outpatient and inpatient settings. We have summarized the patients' psychological issues: logistic overload, loneliness, fear, oxymoronic thoughts, helplessness, frustration, and emotional siege. We describe these psychological threats, provide clinical context for them, and offer practical suggestions for managing them, for the benefit of patients, their caregivers, and clinicians. Our hope is that, by sharing our clinical experience, we can help other oncologists increase their awareness of the psychological impact of the pandemic on cancer patients and implement solutions. Managing these challenges now should translate into improved standards of care when this infective storm is over. Paradoxically, COVID-19 could be an opportunity to learn how to better manage cancer care.